What are The Factors that Influence The Investment Intentions of Generation Z in Yogyakarta? - Ricka Shefyana; Ratih Kusumawardhani; Johannes Maysan Damanik (PT SOLUSI EDUKASI BERDIKARI, 2025)
This study analyzes the factors influencing investment intentions among Generation Z in Yogyakarta by applying the Theory of Planned Behavior (TPB). The variables examined include past behavior and subjective norms toward investment intention. A quantitative approach was employed, with data collected through online questionnaires distributed to 149 Generation Z respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that past behavior has a positive and significant effect on investment intention, with a coefficient of 0,480 (p-value 0,001). Similarly, subjective norms also have a positive and significant effect on investment intention, with a coefficient of 0,451 (p-value 0,002). These findings highlight the importance of prior investment experience and social environment in shaping Generation Z’s investment intentions.